2009
DOI: 10.4103/0028-3886.57822
|View full text |Cite
|
Sign up to set email alerts
|

Common carotid intima-media thickness in acute ischemic stroke: A case control study

Abstract: Stroke is the third leading cause of mortality worldwide. Combined carotid intima-media thickness (CIMT) is a marker of atherosclerosis and is also a predictor for ischemic stroke. We determined the frequency of CIMT in patients with acute ischemic stroke and in matched controls and also the risk factors for CIMT. Sixty patients with ischemic stroke diagnosed by computer tomography (CT) scan and 50 controls matched by age, gender, diabetes, and hypertension were studied. Subjects in both groups underwent carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
18
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 7 publications
9
18
1
1
Order By: Relevance
“…It is believed that thickening of the intima media thickness complex greater than 0.8 mm is abnormal and may represent the earliest changes of atherosclerotic disease (9) .The mean intima media thickness in TIA and stroke patients was 1.1 mm and 0.82 mm respectively. The results showed that mean intima media thickness in our study was slightly greater than that found by Ratnakar Sahoo et al (2009) (10) , where it was 0.78 mm (range 0.5-1.5 mm) in patient group and 0.594 mm (range 0.4-0.9 mm) in controls. In this study 73% and 84% of patients showed evidence of plaques in transient ischaemic attack and stroke group of patients respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…It is believed that thickening of the intima media thickness complex greater than 0.8 mm is abnormal and may represent the earliest changes of atherosclerotic disease (9) .The mean intima media thickness in TIA and stroke patients was 1.1 mm and 0.82 mm respectively. The results showed that mean intima media thickness in our study was slightly greater than that found by Ratnakar Sahoo et al (2009) (10) , where it was 0.78 mm (range 0.5-1.5 mm) in patient group and 0.594 mm (range 0.4-0.9 mm) in controls. In this study 73% and 84% of patients showed evidence of plaques in transient ischaemic attack and stroke group of patients respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…In the study by Sahoo R et al (1) carotid plaques were present in 18 (30%) patients with stroke and 7 (14%) in controls similar to our study, which showed carotid plaques in 17 cases and 6 controls. In the study by Nikic P et al, (3) there was a significant difference in the distribution of plaque status between cases and controls.…”
Section: Discussionsupporting
confidence: 70%
“…While, in the study by Sahoo R et al, (1) the mean carotid intima media thickness in the patient group was 0.782 ± 0.19 mm and 0.594 ± 0.98 mm in control group. Our study showed a higher mean carotid intima media thickness when compared to the above study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doruk et al noticed that there was no significant correlation between age and carotid artery IMT. 16 On the other hand Robin et al reported that IMT was independently and positively related to age. 17 It was also observed that the IMT increased with the duration of diabetes with a significant p value of 0.0218.…”
Section: Discussionmentioning
confidence: 99%